The influence of physical activity programs on the elderly - J. R. Soto; X. Dopico; M. A. Giraldez; F. Iglesias; F. Amador (Asociación Española de Ciencias del Deporte, 2010)
Different institutions affirm that it could show down the declivity of the functional capacities, as result of the old age, by the practice of physical activity make suitable for elderly. The Taiji-Quan, a slow Chinese physical activity, smooth and low physiological work, seems to be a suitable practice for elderly. The main target was to prove if three months of Taiji-Quan practice improve the functional and healthy physical condition of persons above 60 years old. We realized a study with a group of 66 persons, with a mean age of 69,73 years old. We made a control of two hours of Taiji-Quan per week along three months and we made an initial test before the control, and intermediate test and a final postest. The results display statistically significant improvements in the diastolic and systolic blood pressure, in the repose cardiac frequency, in the static and dynamic balance, in the flexibility and in the strength of arms and legs and in the endurance. The Taiji-Quan can be a physical activity suitable for improving the functional and healthy physical condition for elderly. Key Words:  Elderly, physical activity, physical condition and health, taiJi-Quan.